Testing and modeling of a traditional timber mortise and tenon joint - Feio, A. (2014)
Submitted by Paulo Frazão (pfrazao@lnec.pt) on 2014-02-13T16:24:12Z No. of bitstreams: 1 Aref 23 Feio Lourenco and Machado Materials and Structures 2014.pdf: 1087750 bytes, checksum: de819c11f9a2318d3e2d3020f93e81cd (MD5)